Impacts of food safety on beef demand - Marsh, T.L.; Piggott, N.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study investigates whether food safety incidents involving beef, pork, and poultry, and the accompanying publicity have impacted United States meat demand. Beef demand is modeled as a function of beef prices, competing meat prices, meat expenditures, and food safety. Food safety indices are constructed separately for beef, pork, and poultry. Statistical tests reveal significant effects of food safety incidents on beef demand. The effect of an additional beef food safety incident on beef demand is negative, implying a detrimental impact on beef consumption. Spillover effects of pork and poultry safety incidents are positive and improve beef demand, revealing substitution away from pork and poultry towards beef. In other words, food safety incidents involving beef decrease beef demand and those involving pork or poultry increase beef demand. Overall, the demand responses to food safety incidents are small when compared to price effects and to previously reported estimates on health effects, such as information relating to beef and cholesterol.
Keywords: Beef; Beef demand; Food safety; Spillover effects